STUDI KECELAKAAN KAPAL PADA ALUR PELAYARAN BARAT SELAT MADURA, TANJUNG PERAK, SURABAYA - Sumarsono, Sumarsono; Nurhadi, Nurhadi; Yuana, Budy Rolly (Universitas Lambung Mangkurat, 2017)
Among several cruise lines, Madura Strait is one of the densest cruise shipping course that also has a high risk of accidents. According to marine accident report data, in the range of 1995 - 2010 is about 311 marine accidents happened. Accidents due to collision reached 48.5% of total accidents that occur so the impact of collision analysis is important to do. From the source of Pelindo III stated, in period of the 2008-2013, there are 20,582 ship / year passing through Madura strait channel.Traffic based models is an accident frequency calculation approach that tailored to technical standards, environmental conditions, and the density of aquatic traffic in an area. Through this method can be estimated the frequency of collision accidents, aggregates and also the intersection of a specific area. Based on the value of Pc on the Madura Strait (APBS) with the value of Nm, where Nm = 3, there are some values obtained, for Head On obtained Pa = 1.819 E-06, for Crossing obtained Pa = 1.304 E-06 and for Overtaking obtained Pa = 6.299 E-06. Accidents due to Overtaking is the highest accident type of calculation, this is because Pc value is the greatest in APBS path in Inner Channel.